Antimicrobial Efficacy of Aqueous Ozone and Ozone–Lactic Acid Blend on Salmonella-Contaminated Chicken Drumsticks Using Multiple Sequential Soaking and Spraying Approaches - Megahed, Ameer; Aldridge, Brian; Lowe, James (Frontiers in Microbiology, 2020)
Ozone (O3) is an attractive alternative antimicrobial in the poultry processing industry. The optimal operational conditions of O3 for improving food safety concerns are poorly understood. The main objective of this study was therefore to characterize the microbial killing capacity of aqueous-O3 and O3-lactic acid blend (O3-LA) at different operational conditions on chicken drumsticks contaminated with high Salmonella load using sequential soaking and spraying approaches. Four hundred and forty-eight chicken drumsticks (280-310 g) were soaked into two-strain Salmonella cocktail and the initial load on the surface of skin was 6.9-log10 cell forming unit (CFU)/cm2 (95% CI; 6.8 to 7.0). The contaminated drumsticks were then sequentially (10x) soaked and sprayed with aqueous-O3 (8ppm) and O3-LA. Following O3 exposure, quantitative bacterial cultures were performed on the post-saoking and post-spraying water, skin surface, and subcutaneous (SC) of each drumstick using 3M™ Petrifilm™ rapid aerobic count plate (RAC) and plate reader. The average killing capacity of aqueous-O3/cycle on the skin surface was 1.6-log10/cm2 (95% CI; 1.5 to 1.8-log10/cm2) and 1.2-log10/cm2 (95% CI; 1.0 to 1.4-log10/cm2), and in SC was 1.1-log10/cm2 (95% CI; 0.9 to 1.3-log10/cm2) and 0.9-log10/cm2 (95% CI; 0.7 to 1.1-log10/cm2) for soaking and spraying approaches, respectively. Six sequential soaking and seven sequential spraying cycles with ozonated water of 8 ppm reduced the heavy Salmonella load below the detectable limit on the skin surface and SC of drumsticks, respectively. Addition of LA seems to increase the microbial killing capacity of aqueous-O3 with average differences 0.3-log10/cm2 (P=0.08) and 0.2-log10/cm2 (P=0.12) on the skin surface using soaking and spraying approaches, respectively. Aqueous-O3 did not cause any significant changes in the drumstick skin color. The Salmonella load of < 4.5-log10/cm2 was a strong predictor for the reduction rate (P<0.001, R2=0.64). These results provide important information that help the poultry processing facilities for selecting the optimal operational strategy of O3 as an effective antimicrobial.